(untitled) (Tábano, 2025)
The hemlock has gained its fame as the executioner of the legendary Socrates, whose death was a symbol of the importance and, at the same time, the danger of philosophy in a polis. Today, in a world governed by a utilitarian and productivist logic, the hemlock has become more subtle and less theatrical, though no less deadly. In contemporary states, philosophy and the humanities are branded as “useless”, compared to other fields of knowledge capable of providing tangible and marketable results. For these reasons, the humanities have been suffering from cutbacks and defunding in different parts of the world. But is philosophy as useless as the philosophers themselves tend to repeat, and are we not, by repeating this classic mantra, digging our own grave? My thesis is that the futility of philosophy is useless. Futility is nothing more than a refuge, a disguise. As Nietzsche denounced, philosophy for centuries disguised itself as useless and as an ascetic, indifferent to the mundane, in order to legitimize its own work. Paradoxically, its disguise today achieves the opposite effect: the attire that once generated respect and fear before others is today the reason why it is marked as something disposable.